The Use of Instagram as Social Media in the Religious Activities of Majelis Taklim Nurur Rahmah and Its Impact on Social Change - Syamsidar, Cut; Abdullah, Abdullah (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2026)
This study aims to analyze the use of Instagram social media in the religious activities of the Nurur Rahmah Taklim Assembly and its impact on social change within the congregation and the surrounding community. The development of digital technology has encouraged religious institutions to adapt to new media as a means of preaching and disseminating Islamic values. This study uses a qualitative approach with descriptive methods, through data collection techniques such as observation, interviews, and documentation of Instagram account managers and members of the Nurur Rahmah Taklim Assembly. The results show that Instagram is used as an effective da'wah medium through uploading short sermons, quotations from the Quran and hadith, information on religious activities, and documentation of the activities of the Taklim Assembly. The use of Instagram can increase congregational participation, expand the reach of Islamic outreach, and strengthen social interactions between administrators and followers of religious study groups, both online and offline. Furthermore, the use of social media contributes to social change, such as increased religious awareness, changes in religious communication patterns, and the formation of more open and inclusive religious communities. Thus, Instagram plays a crucial role as a supporting medium for religious activities that are relevant to the needs of society in the digital age.